2022
DOI: 10.3390/ijerph19138157
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Walking Limitations on Daily Life: A Mixed-Methods Study of 14 Persons with Late Effects of Polio

Abstract: Reduced walking ability is common in persons with late effects of polio (LEoP). Here, we explored how many walking limitations persons with LEoP perceive, and how these limitations influence daily life, by using a mixed-methods design. Fourteen persons (mean age 70 years, whereof 7 women) with LEoP responded to the Walking Impact Scale (Walk-12), and were interviewed individually. Qualitative data were analysed by systematic text condensation, and each quotation was deductively analysed in relation to the item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, the study found no change in dynamic balance and increased walking safety. In addition, the study concluded that although AFO marginally improved walking ability, it can be a valuable method to enhance daily function 19 . According to the authors of the orthotic management of polio and post-polio syndrome, optimization in cardiorespiratory function and proper orthotic management can be effective methods in managing post-polio syndrome.…”
Section: Discussionmentioning
confidence: 93%
“…However, the study found no change in dynamic balance and increased walking safety. In addition, the study concluded that although AFO marginally improved walking ability, it can be a valuable method to enhance daily function 19 . According to the authors of the orthotic management of polio and post-polio syndrome, optimization in cardiorespiratory function and proper orthotic management can be effective methods in managing post-polio syndrome.…”
Section: Discussionmentioning
confidence: 93%